PERILAKU ETIKA BISNIS PEDAGANG SAYUR DI PASAR TRADISIONAL MANGGISAN TANGGUL PERSPEKTIF ABU HAMID MUHAMMAD AL-GHAZALI: Ethical Business Behavior Of Vegetable Traders In Manggisan Traditional Market Tanggul Abu Hamid Muhammad Al-Ghazali's perspective - Diny Duratul Ummah; Ainul Churria Almalachim (LP2M UIN KH.Achmad Siddiq Jember, 2019)
The Manggisan embankment market is a traditional market where the people conduct daily buying and selling transactions. Conducting business activities does not deny the existence of fraud caused by a lack of awareness and knowledge in doing business based on Islamic business ethics. Every market player must be aware of applying business ethics values. Syari’ah business ethics is a moral reference as part of Islamic forms of Akhlaqul Karimah in muamalah. Islamic business ethics is based on monotheism, honesty, justice (balance), and kindness (ihsan). In conducting business activities, Abu Hamid Muhammad Al Ghazali emphasized always being guided by Islamic business ethics because by doing so, a Muslim doing his business will get two advantages, namely the world and the hereafter. The formulation of the problem from this study is how the behavior of the vegetable traders' ethics in the embankment Manggisan market. And how the behavior of greengrocer business ethics in the market of Abu Hamid Muhammad Al Ghazali’s embankment perspective. This research is a type of (field research) using empirical juridical methods. These methods collect data using observation, interviews, and documentation of the behavior of business ethics of vegetable traders in business activities. Based on the result of the study, it can be concluded that, in general, the vegetable traders in the Manggisan embankment market have applied business ethics behavior in their business activities. Including starting a business by reading basmalah, not reducing scales, and not taking very much profit, even though, in reality, they do not understand that what they are doing is part of the theory of business ethics. But there are still traders who sometimes are rude to buyers due to having personal problems with their families; this is considered to have violated Islamic business ethics. One of the principles that a Muslim trader must possess is to be good so that what is done will provide benefits to others so that the business carried out does not only benefit themselves but also benefits others.